The Influence of Public Communication Through Instagram on Plastic Waste Management on Community Knowledge and Behavior in Medan Tuntungan Sub-District, Medan City - Sihombing, Tina Silvia Romauli; Asmara , Sakhyan; Kurniawati , Dewi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to see the use of public communication through Instagram, knowledge, and behavior of the community in plastic waste management. The results showed that the Medan Tuntungan sub-district government had carried out public communication in the very effective category, knowledge of plastic waste management in the good category and community behavior in plastic waste management was effective. The results of simple linear regression analysis to test the relationship between public communication through Instagram on public knowledge in plastic waste management show there is a positive and significant influence with a correlation coefficient of 0.826. If the correlation coefficient value is converted to the Guilford scale, it is known that the correlation between variables is in the very strong category. The results of simple linear regression analysis to test the relationship between public communication through Instagram on public behavior in plastic waste management show a positive and significant influence between with a correlation coefficient of 0.707. If the correlation coefficient value is converted to the Guilford scale, it is known that the correlation coefficient is in the strong category.